The role of interleukin-1β in type 2 diabetes mellitus: A systematic review and meta-analysis - Alfadul, Hend; Sabico, Shaun; Al-Daghri, Nasser M. (Frontiers in Endocrinology, 2022)
Type 2 diabetes mellitus (T2DM) is a multifactorial non-communicable disease that is characterized by insulin resistance and chronic sub-clinical inflammation. Among the emerging inflammatory markers observed to be associated with β-cell damage is interleukin 1β (IL1β), a proinflammatory cytokine that modulates important metabolic processes including insulin secretion and β-cell apoptosis. The present systematic review and meta-analysis gathers available evidence on the emerging role of IL1β in T2DM. PubMed and Embase were searched for human studies that assessed 1L1β in T2DM individuals from 2016-2021. Thirteen studies (N=2680; T2DM=1182, controls=1498) out of 523 were included in the systematic review and only 3 studies in the meta-analysis. Assays were the most commonly used quantification method and lipopolysaccharides as the most common stimulator for IL1β upregulation. Random and fixed effects meta-analysis showed non-significant mean differences of IL1β concentrations between the T2DM and controls. Given the high heterogeneity and small subset of studies included, caution is advised in the interpretation of results. The present systematic review and meta-analysis highlights the limited evidence available that could implicate 1L1β as a potent biomarker for T2DM. Standardization of 1L1β assays with larger sample sizes are encouraged in future observational and prospective studies.